POST COVID-19: TEACHER CHALLENGES AND INNOVATIONS IN LEARNING - Kurniawan, Angga; Ihsan, Ikhlasul; Ikhwana, Ikhwana; Pratama Ilyas, Vickry; Mavianti, Mavianti (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine the learning constraints of the school. During the covid 19 pandemic. The type of research used is descriptive qualitative suffering. The subjects of his research were the parents of students and students. The object of the research is the mental condition of students during the Covid 19 pandemic.The research method used is qualitative research with literature review methods. Data collection was carried out by tracing various sources in the form of government documents, mass media and previous relevant research results were analyzed using principles and supported by the results of interviews with several students and teachers. The results of this study indicate that government policies in tackling the spread of the Corona virus have an impact on the emergence of new concepts related to learning innovations that can be applied. The method is online. It is hoped that technology-based learning innovations will not only take place during the Covid-19 pandemic but can be applied after Covid-19 ends for more advanced and quality education.The results of the analysis show that the obstacles experienced by students in online learning include decreased learning motivation due to boredom, lack of understanding of material due to limited facilities. Barriers to parents include economic conditions affected by the COVID-19 pandemic that do not support learning, and lack of time to accompany students. Barriers to teachers include lack of knowledge and skills regarding technology and limited learning interactions. Meanwhile, obstacles from educational institutions include re-planning and supervision which are hampered in the implementation of online learning. This study aims to determine the learning constraints from schools that become obstacles for teachers/students in the teaching and learning process. It is hoped that technology-based learning innovations will not only take place when the Covid-19 pandemic ends, for education to be more advanced and of high quality.